Addressing the overuse of hospital emergency departments in the Portuguese NHS - Goiana-da-Silva, Francisco (2024)
Publisher Copyright: Copyright © 2025 Goiana-da-Silva, Costa, Malcata, Sá, Vasconcelos, Cabral, Guedes, Morais-Vilaça, Pinheiro-Guedes, Ferreira, Pereira, Gaspar-Pais, Neves, Monteiro, Pires, Paiva, Guimarães, Ashrafian, Moreira, Fonseca, Cardoso, Alves, Darzi and Araújo.